High-Resolution Diffusion-Weighted Imaging of Neck Lymph Nodes Using 2D-Single-Shot Interleaved Multiple Inner Volume Imaging Diffusion-Weighted Echo-Planar Imaging at 3T - Park, J.K.; Kim, S.-E.; Trieman, G.S.; Parker, D.; Jeong, E.-K. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: 2D-ss-IMIV-DWEPI is an ss-DWEPI with greatly reduced geometric distortion. The purposes of this paper are to 1) evaluate of the utility of 2D-ss-IMIV-DWEPI for high-resolution neck LN imaging; 2) determine whether 2D-ss-IMIV-DWEPI can depict normal LN hilum; and 3) evaluate whether the inclusion of LN hilum within ROIs affects the measured LN ADC. MATERIALS AND METHODS: HR-DWI was acquired with 1-mm2 in-plane resolution and 2-mm section thickness by using 2D-ss-IMIV-DWEPI. In total, 58 LNs from 18 subjects were evaluated. The ADC map was calculated by using DWI with b = 10 and 300 s/mm2. In those LNs where the LN hilum could be recognized, the LN ADC was measured with and without inclusion of the hilum, and the mean difference of the resulting ADC values was determined. RESULTS: The hilar structure was identified by DWI in 15 LNs. The ADC of the hilum was 1.981 ± 0.331 × 10−3 mm2/s. In these 15 LNs, the ADC value excluding hilar structure was significantly lower than the ADC value including hilar structure (0.983 ± 0.169 versus 1.206 ± 0.244 × 10−3 mm2/s; P < .0001). The mean ADC in a total of 58 LNs excluding the hilar structure was significantly lower than the value obtained including the hilar structure (1.034 ± 0.183 versus 1.095 ± 0.213 × 10−3 mm2/s; P = .0002). CONCLUSIONS: HR-DWI of neck LNs obtained by using 2D-ss-IMIV-DWEPI could identify the hilar structure. The ADC of normal neck LNs seemed significantly different when the hilum was included. The results suggest that HR-DWI may be helpful to aid selection of proper ROIs within LNs for accurate and reliable ADC measurements. ADCapparent diffusion coefficientDWIdiffusion-weighted imagingEPIecho-planar imagingHRhigh-resolutionLNlymph nodePEphase-encodingRFradio frequencyROIregion of interestSNRsignal-to-noise ratio2D-ss-IMIV-DWEPI2D-single-shot interleaved multiple inner volume imaging diffusion-weighted echo-planar imaging